Effect of crystal pre-straining on phonon damping of dislocations - Petchenko, A.M.; Petchenko, G.A. (Functional Materials, 2008)
The damped dislocation resonance in KBr crystals at 0.75 % residual strain has been studied in the 77 to 300 K temperature range using the pulsed echo technique. The sample strain change has been found to influence considerably the dislocation resonance localization but does not affect the absolute value of viscosity coefficient B and its temperature dependence. Basing on the frequency spectra and temperature dependences of other quantities, the temperature-dependent variations of the dislocation damping factor, B, and the average effective length of the dislocation segment, L, were determined within the mentioned temperature range. The dislocation fixation process in the crystals at 0. 75 % residual strain at temperature lowering has been found to be controlled by the simultaneous action of weak and strong stoppers. Comparing the experimental B(T) dependence with theoretical curve calculated using the Alshits-Indenbom theory, it has been established that the viscous dislocation damping in KBr crystals is limited by superposition of phonon wind and "slow" phonon relaxation mechanisms.